Sporen. (Hasselt : Provinciaal Museum, 1986)
Twombly, Cy ; Manzoni, Piero ; Duchamp, Marcel ; Beuys, Joseph ; Pollock, Jackson ; Judd, Donald ; Kosuth, Joseph ; Weiner, Lawrence ; Rainer, Arnulf ; Long, Richard
Sporen, Provinciaal Museum, Hasselt, 22.3. - 20.4.'86
boek